Harnessing screw dislocations in shell-lattice metamaterials for efficient, stable electrocatalysts - Liqiang Wang; Di Yin; James Utama Surjadi; Junhao Ding; Huangliu Fu; Xin Zhou; Rui Li; Mengxue Chen; Xinxin Li; Xu Song; Johnny C. Ho; Yang Lu (Nature Communications)
Abstract Developing highly active and robust catalysts remains a critical challenge for the industrial realization and implementation of nitrate reduction. Here, we proposed a screw dislocation-mediated three-dimensional (3D) printing strategy for scalable, integrated manufacturing of metamaterial catalysts. Specifically, screw dislocation was introduced into the 3D printing process to mediate the simultaneous synthesis of 3D architecture and chiral surface nanostructures, effectively eliminating conventional heterointerfaces. Additionally, severe strain effects induced by dislocation multiplication in curved spaces enhance intrinsic catalytic activity by promoting NO3 − adsorption and lowering the energy barrier of NO3 −-to-NH3 conversion. Consequently, the FeCoNi dual-scale shell-lattice metamaterials with high dislocation density achieve a Faraday efficiency of 95.4%, an NH3 yield rate of 20.58 mg h−1 cm−2, and long-term stability exceeding 500 hours. A flow-through electrolyzer coupled with an acid absorption unit successfully produced NH4Cl fertilizer products. Our work opens a new perspective for advancing 3D printing technology in catalysis applications.